(untitled) (Revista Brasileira de Pesquisa em Saúde/Brazilian Journal of Health Research, 2018)
Semantic equivalence of the Portuguese version of the Memorial Symptom Assessment Scale (MSAS) to evaluate symptoms in cancer patients